Representing the Black female subject in western art - Nelson, Charmaine (Routledge studies on African and Black diaspora, 2010)
Nelson analyzes not only how, where, why and by whom black female subjects have been represented in Western art, but also what the social and cultural impacts of the colonial legacy of racialized Western representation have been. She poses questions about the concepts of production, the consequences of comsumption and more
Keywords: afro-féminisme; approches et analyses; arts; cours; discipline; féminisme afroaméricain; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; racisme; représentation des femme*; représentation des femmes* racisées; ressource en ligne; système colonial; systèmes d'oppressions; thématiques